PENINGKATAN DAYA SAING MELALUI PEMASARAN INOVATIF, EFISIENSI OPERASIONAL DAN MANAJEMEN SDM DI UMKM GULA BOROBUDUR - Yusuf Rahman Al Hakim; Surya Adi Winata; Nurhidayat Nurhidayat (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Micro and small enterprises based on local culture have great potential in supporting the regional economy and educational tourism development. Gubuk Kopi Borobudur is a traditional Javanese sugar processing MSME in Sendaren I Hamlet, Borobudur District, Magelang Regency, which integrates traditional production processes with cultural tourism concepts. This Field Work Practice aimed to analyze business management conditions, identify main problems, and formulate strategic recommendations for competitiveness enhancement. The method used was a qualitative descriptive approach through observation, interviews, and documentation conducted from November 29 to December 1, 2025. The results identified five main problems: raw material instability, product quality inconsistency, high production costs, labor limitations, and suboptimal marketing strategies. The formulated strategic recommendations include supplier diversification, production process standardization, operational efficiency improvement, youth involvement, and innovative marketing development that are applicable and can be implemented gradually without eliminating traditional values.